Thoracic injuries in professional rugby players: mechanisms of injury and imaging characteristics - Hayashi, Daichi; Roemer, Frank; Kohler, Ryan; Guermazi, Ali; Gebers, Chris; De Villiers, Richard (British Journal of Sports Medicine, 2014)
Professional rugby players are prone to traumatic thoracic injuries due to the use of minimal protective gear to cover the torso. In the 2007 Rugby World Cup, thoracic injuries occurred at a rate of 8.3 cases/1000 player-hours. CT and MRI play an important role in the diagnosis of these injuries. Vital internal organs, such as the heart, lungs, trachea, liver and large blood vessels lie within close proximity to the bony structures and what seems to be a simple rib fracture or clavicular dislocation can have potentially life-threatening complications that are not detected by conventional radiography. Cross-sectional imaging helps to determine the choice of treatment. Ultrasound offers a quick and dynamic imaging examination and allows high-resolution assessment of superficial tissues that complements conventional imaging. In this review article, we (1) presented data on incidence of thoracic injuries in professional rugby players; (2) described the anatomy of the joints comprising the thoracic cage and major muscles attached to the rib cage; (3) discussed indications and relevance for MRI and presented an optimised MRI protocol for assessment of suspected thoracic injury; and (4) illustrated various types of thoracic injuries seen in professional rugby players, including sternal contusion, retrosternal haematoma, manubriosternal disruption, sternoclavicular dislocation, rib fractures and injuries of the pectoralis major muscle.
EVALuna2:14395